Efficacy and Safety of Switching Prostaglandin Analog Monotherapy to Tafluprost/Timolol Fixed-Combination Therapy - Kazuyoshi Kitamura; Tatsuya Chiba; Fumihiko Mabuchi; Kiyotaka Ishijima; Shu Omoto; Fumiko Kashiwagi; Takashi Godo; Satoshi Kogure; Teruhiko Goto; Takashi Shibuya; Jhoji Tanabe; Shigeo Tsukahara; et al. (Journal of Ophthalmology)
Purpose. To assess the efficacy and safety of switching from prostaglandin analog (PGA) monotherapy to tafluprost/timolol fixed-combination (Taf/Tim) therapy. Subjects and Methods. Patients with primary open-angle glaucoma, normal-tension glaucoma, or ocular hypertension who had received PGA monotherapy for at least 3 months were enrolled. Patients were examined at 1, 2, and 3 months after changing therapies. Subsequently, the patients were returned to PGA monotherapy. The examined parameters included intraocular pressure (IOP) and adverse events. A questionnaire survey was conducted after the switch to Taf/Tim therapy. Results. Forty patients with a mean age of 66.5 ± 10.3 years were enrolled; 39 of these patients completed the study protocol. Switching to Taf/Tim significantly reduced the IOP from 18.2 ± 2.6 mmHg at baseline to 14.8 ± 2.5 mmHg at 1 month, 15.2 ± 2.8 mmHg at 2 months, and 14.9 ± 2.5 mmHg at 3 months (P<0.001). Switching back to the original PGA monotherapy returned the IOP values to baseline levels. Taf/Tim reduced the pulse rate insignificantly. No significant differences were observed in blood pressure, conjunctival hyperemia, or corneal adverse events. A questionnaire showed that the introduction of Taf/Tim did not significantly influence symptoms. Conclusions. Compared with PGA monotherapy, Taf/Tim fixed-combination therapy significantly reduced IOP without severe adverse events.